Environmental & architectural phenomenology. Vol. 30, Number 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2018)
Vol. 30, No. 1, Winter/Spring 2019 (Besides “conferences,” “items of interest,” and “citations received,” this EAP issue includes the following entries: an “in memoriam” for geographer David Lowenthal, an early figure in environmental phenomenology, who died in London in September; a “book note” on architect and architectural theorist Hendrik Auret’s Christian Norberg-Schulz’s Interpretation of Heidegger’s Philosophy (Routledge, 2018); a “book note” on philosopher Edward Casey’s The World on Edge (Indiana University Press, 2017); the second part of the late philosopher Henri Bortoft’s 1999 conference presentation on Goethean science; Anthropologist Jenny Quillien’s reflections upon her recent experiences of living in Amsterdam as they point toward the significance of language in contributing to places and lifeworlds; Colorado speedskater David Feric’s account of his firsthand experience of the sport as a starting point for a phenomenology of speedskating; Artist and art educator Doris Rohr’s consideration of the work of British artist and art critic John Ruskin as a conceptual and methodological means to facilitate a style of seeing and drawing that maintains sympathetic contact with the thing looked at and represented.
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals